Determination of enantiomeric excess of leucine and valine by X-ray powder diffraction - Tadeusiak, Elżbieta; Kruszynski, Rafal; Trzesowska-Kruszynska, Agata; Sieranski, Tomasz; Lewinski, Bartlomiej (European Journal of Chemistry, 2010)
Two amino acids, leucine and valine, were studied by X-ray powder diffraction (XRPD). The linear correlations between intensity of racemate (decrease) or enantiomer (increase) and enantiomeric excesses were observed in each case.